Gaya Kepemimpinan Kepala Desa dalam Meningkatkan Partisipasi Masyarakat pada Program Pembangunan Fisik Desa - T. Egho, Febrianus; Putu Yoga Bumi Pradana , I; Petrus Sayrani, Laurensius (Policy, Law and Political Research Center, 2023)
This research aims to determine the leadership style and the factors behind the village head's leadership in increasing community participation in village development and to determine the stages of community participation in Tarawali Village. This research uses a qualitative method with a descriptive approach. The selection of informants used a purposive sampling technique. The findings show that: 1) the leadership style as assessed by the construction of irrigation, farming roads and houses of worship in Tarawali Village has quite good communication, good responsibility and good motivation, but on average, community participation is still lacking due to the leadership role the village head is considered not optimal; 2) types of community participation in Tarawali Village, namely initiative participation, legitimacy and execution. This research discusses leadership styles related to communication focus, responsibility and motivation. The originality is that this research discusses the factors behind the less-than-optimal development process in more depth. In addition, this research identifies types of community participation. This research has limitations in the number of informants and simple question instruments.